Hypertension care cascade in an urban resettlement colony and slum in Delhi, India: a cross-sectional survey - Mongjam Meghachandra Singh; Saurav Basu; Heena Lalwani; Shivani Rao; Vansh Maheshwari; Sandeep Garg; Nandini Sharma (BMC, 2023)
Abstract Background Hypertension care cascade in resource-limited settings is compromised with a majority of patients with hypertension remaining undiagnosed, untreated, non-adherent, and poorly controlled at every stage. However, there is paucity of information on care and management of hypertensive patients in community-based settings of low-income urban neighbourhoods in India. Methods This was a community-based cross-sectional study conducted in an urban resettlement colony and slum area in the Northeast District of Delhi. The adult population was screened for hypertension using standardized methods, and adherence to medications was assessed using the Morisky Green Levine scale. Binary logistic regression analysis was conducted to ascertain the sociodemographic predictors of the outcome (presence of hypertension, adherence to antihypertensive medication, blood pressure control). A p-value < 0.05 was considered statistically significant. Results We included 8850 adult participants including 5295 females and 3555 males in this study. Nearly 29% of the participants were hypertensive, of which 61.77% were newly diagnosed cases. Furthermore, nearly 81% of the previously diagnosed cases had been initiated on antihypertensive medication, of which 57.54% were adherent to their medications while 36.12% attained controlled blood pressure levels. The odds of having hypertension were significantly higher among males (AOR = 1.87, 95% CI: 1.63 to 2.15), age ≥ 60 years (AOR = 9.15, 95% CI: 7.82 to 10.70), high waist circumference (AOR = 2.24, 95% CI: 1.86 to 2.70) and Body Mass Index of ≥ 25.00 (AOR = 2.55, 95% CI: 2.00 to 3.26). Furthermore, on adjusted analysis, patients of hypertension having diabetes (DM) comorbidity had significantly higher odds of being adherent to anti-hypertensive medications (AOR = 1.81, 95% CI: 1.31 to 2.51) compared to those without DM comorbidity, while tobacco users had significantly lower odds of being adherent to antihypertensive medication (AOR = 0.50, 95% CI: 0.31 to 0.82). Conclusions Hypertension care cascade in urban slum-resettlement colony setting revealed a high burden of undiagnosed hypertension, low rates of medication adherence, and poor blood pressure control. Strengthening community screening and primary care continuum of care is necessary to improve the hypertension care cascade from early diagnosis to effective management with optimal health outcomes to reduce patient complications and increase longevity.